Peranan Penggunaan Informasi Akuntansi Umkm Sektor Sasirangan Pada Kampung Sasirangan Seberang Masjid Dan Sungai Jingah Kota Banjarmasin - Yustisiana Sari; Kadir, Kadir; Muhammad Hudaya (Edunomics Journal, 2024)
Micro, Small and Medium Enterprises (MSMEs) have a very important role in development in Indonesia. This study aims to determine the phenomenon of accounting practices and the role of accounting information on the success of Sasirangan UMKM. This type of research is qualitative research using a phenomenological approach. The subjects of this study were Sasirangan SMEs in Sasirangan Sungai Jingah Village and Opposite the Mosque in Banjarmasin City, namely 14 respondents. Data collection techniques in this study used interview, observation, and documentation techniques. The data analysis stage in this study consisted of data collection, data reduction, data display, and decision making. The results showed that accounting information has a role in the success of MSME businesses, namely in determining the purchase of inventory, determining the selling price, increasing business capital, implementing the production of goods and providing debt to customers. The results of other studies indicate that most MSMEs do not carry out accounting practices due to the informants' lack of understanding of accounting and the informants' lack of awareness of the role of accounting